African indigenous knowledges in a postcolonial world : essays in honour of Toyin Falola - Falola, Toyin; Yacob-Haliso, Olajumoke; Nwogwugwu, Ngozi; Ntiwunka, Gift (Abingdon, Oxon ; New York, NY : Routledge, 2021)
This book argues that ancient and modern African indigenous knowledges remain key to Africa's role in global capital, technological and knowledge development and to addressing her marginality and postcoloniality. The contributors engage the unresolved problematics of the historical and contemporary linkages between African knowledges and the African academy, and between African and global knowledges. The book relies on historical and comparative political analysis to explore the global context for the application of indigenous knowledges for tackling postcolonial challenges of knowledge production, conflict and migration, and women's rights on the continent in transcontinental African contexts. Asserting the enduring potency of African indigenous knowledges for the transformation of policy, the African academy and the study of Africa in the global academy, this book will be of interest to scholars of African Studies, postcolonial studies and decolonisation and global affairs.
OCLC-licensed vendor bibliographic record.
Keywords: Ethnoscience -- Africa; Ethnophilosophy -- Africa; Knowledge, Sociology of; Africa -- Social life and customs; Africa -- Intellectual life; HISTORY / Africa / General